Are transventricular approaches associated with increased hemorrhage?: A comparative study in a series of 624 deep brain stimulation surgeries - Runge, Joachim; Nagel, Johanna M.; Cassini Ascencao, Luisa; Blahak, Christian; Kinfe, Thomas M.; Schrader, Christoph; Wolf, Marc E.; Saryyeva, Assel; Krauss, Joachim K. (Operative neurosurgery, 2022)
BACKGROUND: Deep brain stimulation (DBS) surgery has advanced tremendously, for both clinical applications and technology. Although DBS surgery is an overall safe procedure, rare side effects, in particular, hemorrhage, may result in devastating consequences. Although there are certain advantages with transventricular trajectories, it has been reasoned that avoidance of such trajectories would likely reduce hemorrhage. OBJECTIVE: To investigate the possible impact of a transventricular trajectory as compared with a transcerebral approach on the occurrence of symptomatic and asymptomatic hemorrhage after DBS electrode placement. METHODS: Retrospective evaluation of 624 DBS surgeries in 582 patients, who underwent DBS surgery for movement disorders, chronic pain, or psychiatric disorders. A stereotactic guiding cannula was routinely used for DBS electrode insertion. All patients had postoperative computed tomography scans within 24 hours after surgery. RESULTS: Transventricular transgression was identified in 404/624 DBS surgeries. The frequency of hemorrhage was slightly higher in transventricular than in transcerebral DBS surgeries (15/404, 3.7% vs 6/220, 2.7%). While 7/15 patients in the transventricular DBS surgery group had a hemorrhage located in the ventricle, 6 had an intracerebral hemorrhage along the electrode trajectory unrelated to transgression of the ventricle and 2 had a subdural hematoma. Among the 7 patients with a hemorrhage located in the ventricle, only one became symptomatic. Overall, a total of 7/404 patients in the transventricular DBS surgery group had a symptomatic hemorrhage, whereas the hemorrhage remained asymptomatic in all 6/220 patients in the transcerebral DBS surgery group. CONCLUSION: Transventricular approaches in DBS surgery can be performed safely, in general, when special precautions such as using a guiding cannula are routinely applied.
Gesehen am 27.08.2024